(untitled) (CIPEEX, 2023)
THIS PROJECT ADDRESSES THE CONCEPT OF THE MATERIALIZATION OF INDIGENOUS TERRITORIAL RIGHTS BASED ON THE THEORY OF INDIGENATO PROMOTED IN THE INTER-AMERICAN COURT OF HUMAN RIGHTS AND THE BRAZILIAN COURTS, PRESENTING THE FORMATION OF SPIRITUAL ELEMENTS IN THE CULTURAL CONCEPTION OF LAND. THE AIM OF THE RESEARCH WILL BE TO DEBATE THE RIGHTS OF INDIGENOUS PEOPLES TO POSSESSION AND PROPERTY IN CONFRONTATION WITH THE THESIS OF THE TEMPORAL FRAMEWORK OF OCCUPATION AS A LOGICAL LEGAL INTERPRETATION IN THE ACTIONS BROUGHT BEFORE THE IACHR, AS WELL AS IN THE ANALYSIS OF THE CASES BEFORE THE FEDERAL SUPREME COURT AND THE BRAZILIAN COURTS. THE PROBLEMATIZATION OF THE RESEARCH WILL BE CENTERED ON THE THEME OF HOW THE LOGICAL LEGAL ARGUMENTATION OF POSSESSION AND PROPERTY IS FORMED FROM THE THEORY OF INDIGENEITY AND TO WHAT EXTENT THE COLLECTIVE RIGHT TO INDIGENOUS PROPERTY AFFIRMED BY SPIRITUAL STRUCTURES IS ESTABLISHED. THE METHODOLOGY THAT WILL BE USED IS A QUALITATIVE AND INDUCTIVE APPROACH, BASED ON THE ANALYSIS OF CONCRETE AND COMPARATIVE CASES JUDGED BY THE IACHR AND BRAZILIAN COURTS THAT CORRELATE THE THEORY OF INDIGENEITY VERSUS THE THEORY OF INDIGENOUS FACT, USING DOCUMENTARY ANALYSIS AND INTERPRETATION TECHNIQUES. THE METHODS THAT WILL BE DEVELOPED ARE: COMPOSITIONAL, MONOGRAPHIC AND HISTORICAL. THE AIM OF THE RESEARCH IS TO VERIFY THE POSSIBLE LOGICAL LEGAL ARGUMENTS THAT ARE BEING DISCUSSED IN THE IACHR AND THE BRAZILIAN COURTS REGARDING THE POSSESSION OF INDIGENOUS PEOPLES AS AN AFFIRMATION OF TERRITORIAL RIGHTS, AS WELL AS TO PROVIDE THE INDIGENOUS COMMUNITY WITH LEGAL CERTAINTY IN THE ARGUMENT OF POSSESSION, PROPERTY, SOCIAL FUNCTION AND THE EXERCISE OF THE PRESERVATION OF THE CULTURE OF INDIGENOUS PEOPLES AND THEIR STRUCTURAL ELEMENTS FOCUSED ON BELIEFS.